Girls think of everything : stories of ingenious inventions by women - Thimmesh, Catherine (Houghton Mifflin Harcourt, 2018)
Tells the story of how women throughout the ages have responded to situations confronting them in daily life by inventing such items as correction fluid, space helmets, and disposable diapers.